Implementing Smoke-Free Hospital Policy in Bali: An Edward III Framework Analysis - Ida Bagus Putu Adi Sentanu; Wayan Astawa; Cokorda Putra Indrayana (Journal of Multidisciplinary Academic and Practice Studies, 2026)
Purpose: This study examines the implementation of Bali Provincial Regulation No. 10/2011 on Smoke-Free Areas at Prof. dr. I Goesti Ngoerah Gde Ngoerah Regional General Hospital in Denpasar through the lens of Edward III's policy implementation framework. Research Methodology: A qualitative descriptive design was used, drawing on purposive sampling of six key informants from hospital management, the occupational health and safety committee, nursing staff, support workers, and visitors. Data were gathered through in-depth interviews, direct observation, and document review, then analyzed through data reduction, display, and conclusion drawing, with triangulation across sources. Results: Bureaucratic structure and disposition performed comparatively well, supported by an established monitoring unit and generally favorable staff attitudes, while communication and resources lagged behind, marked by limited socialization reach, insufficient monitoring personnel, and the absence of a hospital-wide public address system. Conclusions: Structural and attitudinal foundations exist, but the hospital's ability to translate the regulation into consistent visitor compliance depends on intensifying communication and strengthening resource allocation. Limitations: The single-site design, small informant pool, and cross-sectional nature restrict generalizability and preclude tracking of change over time. Contributions: The study extends Edward III's framework to a Balinese healthcare setting, offers practical recommendations for hospital administrators, and adds an underrepresented regional case to the national literature on tobacco control implementation in Indonesia.